2020
DOI: 10.1002/ppp.2080
|View full text |Cite
|
Sign up to set email alerts
|

Study on the mechanism of crystallization deformation of sulfate saline soil during the unidirectional freezing process

Abstract: The freezing of sulfate saline soil involves the coupling effect of heat and mass transfer and crystallization deformation. The influence of salt content and temperature on the crystallization of ice and salt was analyzed by using a one‐side freezing experiment. Based on the effect of solute and temperature on water activity, a crystallization kinetics model of ice–water phase change in saline soil was established. The application of supersaturation in the crystallization kinetics model of solution–crystal pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…where the height is the distance from the bottom of the soil column where the salt starts to precipitate. The graph shows that the salt first starts to precipitate from the top of the soil column [15][16][17][18] . During the experiment, as the temperature rises the water is gradually evaporated, so that the content of salt in the solution inside the soil column is higher than the solubility, thus causing the salt to crystallize and precipitate 19,20 .…”
Section: Resultsmentioning
confidence: 99%
“…where the height is the distance from the bottom of the soil column where the salt starts to precipitate. The graph shows that the salt first starts to precipitate from the top of the soil column [15][16][17][18] . During the experiment, as the temperature rises the water is gradually evaporated, so that the content of salt in the solution inside the soil column is higher than the solubility, thus causing the salt to crystallize and precipitate 19,20 .…”
Section: Resultsmentioning
confidence: 99%
“…Pore distribution is an inherent property of soil particles and can be measured by Mercury intrusion porosimetry, Nuclear Magnetic Resonance spectroscopy method, etc. ; Pore water activity is controlled by ion species and their concentrations, which can be determined based on the Pitzer theory (Pitzer, 1991;J. Zhang, 2020).…”
Section: The Developed Modelmentioning
confidence: 99%
“…J. Spencer (J. Zhang, 2020) fitting method by real calculations. We found that the former was better than the latter.…”
Section: Water Activity Of the Pore Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Salt heaving mainly occurred in the later period of saline soil with low salt content. e higher the soluble salt content, the smaller the thermal conductivity and permeability coefficient of the soil sample [27] and the greater the contribution of salt swelling to soil deformation [13,28,29]. At the same time, salt also migrated with water and be excluded to unfrozen water in the freezing process.…”
Section: Introductionmentioning
confidence: 99%